(untitled) (Journal of Humanities and Social Sciences Research, 2023)
Efflux pump genes are an important resistance mechanism that may be specific for one substrate or may transport a range of structurally dissimilar compounds. Efflux pumps represent an important and large group of transporter proteins found in almost all organisms. In this study, potential mechanisms underlying resistance of Listeria monocytogenes to humans’ intestinal bile were investigated. These results indicated that listeria monocytogenes efflux pump genes have a critical role in the resistance and survival of this pathogen to human bile and other antibacterial components. The efflux pumps reside in their ability to extrude a wide range of antibiotics, resulting in the emergence of multidrug resistance in many bacteria. Besides antibiotics, efflux pumps can also extrude a large variety of compounds.